The time is fulfilled five aspects of the fulfilment of the Old Testament in the New - Bruce, Frederick Fyvie, 1910-90; Moore Theological College, Sydney, Australia (Exeter, UK Paternoster, 1978)
Includes bibliographical references and indexes.
Inaugural series of annual Moore College Lectures, September, 1977
Keywords: Bible. N.T. -- criticism, interpretation, etc